Pandemics and communication: an experimental assessment - Melo,Carolina (2020)
Abstract Communication is a key factor in containing a pandemic. Fragmented information may affect people’s perceptions and behaviors, especially in times of governmental miscommunication, potentially jeopardizing efforts aimed at containing the spread of the disease. To test whether and how people have been sensitive to broken information during the COVID-19 pandemic in Brazil, we performed a randomized survey experiment on a sample of 571 respondents. We found that more pessimistic or more optimistic fragmented messages about the pandemic have no overall significant average effect on perceptions and planned behavior of the respondents. The exploratory analyses showed that particular sociodemographic groups are more sensitive to these fragmented messages. While less educated people react to more pessimistic messages with an increased likelihood to intensify prevention measures, people aged 60 or older - the high-risk group for COVID-19 complications - react to more optimistic messages with a reduced probability to intensify prevention measures. Besides providing insights to the public administration literature on disaster management, the results reinforce the need for governments to consistently centralize communication efforts to guarantee that people are equipped with complete and accurate information to form their perceptions and adequate their behaviors towards a health crisis.